Silicon Nitride Spot-Size Converter with Coupling Loss < 1.5 dB for Both Polarizations at 1W Optical Input - Enge Zhang; Yu Zhang; Lei Zhang; Xu Yang (Photonics)
Microwave photonics (MWP) applications often require a high optical input power (>100 mW) to achieve an optimal signal-to-noise ratio (SNR). However, conventional silicon spot-size converters (SSCs) are susceptible to high optical power due to the two-photon absorption (TPA) effect. To overcome this, we introduce a silicon nitride (SiN) SSC fabricated on a silicon-on-insulator (SOI) substrate. When coupled to a tapered fiber with a 4.5 μm mode field diameter (MFD), the device exhibits low coupling losses of <0.9 dB for TE modes and <1.4 dB for TM modes at relatively low optical input power. Even at a 1W input power, the additional loss is minimal, at approximately 0.1 dB. The versatility of the SSC is further demonstrated by its ability to efficiently couple to fibers with MFDs of 2.5 μm and 6.5 μm, maintaining coupling losses below 1.5 dB for both polarizations over the entire C-band. This adaptability to different mode diameters makes the SiN SSC a promising candidate for future electro-optic chiplets that integrate heterogeneous materials such as III-V for gain and lithium niobate for modulation with the SiN-on-SOI for all other functions using advanced packaging techniques.